2007
DOI: 10.1080/13875860701608368
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctions of Spatial Cognition in Schizophrenic Patients

Abstract: Twenty outpatients who fulfilled the criteria for a diagnosis of schizophrenia and 28 control participants were invited to learn a route through a complex outdoor environment. They were then tested in tasks intended to explore various aspects of their memorized representation of the navigational episode. Compared to controls, the patients showed significant impairment in both the verbal production of route directions and the drawing of sketch maps. They referred to fewer landmarks and provided fewer directiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…By contrast, more than half of the participants of the CA group were able to describe the route correctly in the two experiments, and 9 participants out of 17 were able to correctly draw the route on the map in Experiment 2. This proportion was not high but, as regards to route descriptions, it was comparable to those observed in experiments conducted in real environments (see Daniel et al, 2007;Denis et al, 2014). Research with adults has also shown that there are large individual differences in the microgenesis of environmental knowledge (Ishikawa & Montello, 2006).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…By contrast, more than half of the participants of the CA group were able to describe the route correctly in the two experiments, and 9 participants out of 17 were able to correctly draw the route on the map in Experiment 2. This proportion was not high but, as regards to route descriptions, it was comparable to those observed in experiments conducted in real environments (see Daniel et al, 2007;Denis et al, 2014). Research with adults has also shown that there are large individual differences in the microgenesis of environmental knowledge (Ishikawa & Montello, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…The first and the second route descriptions were transcribed and coded as a set of minimal units of information, following the method used by Denis (1997). In the original classification, Denis and his collaborators divided the unit of information into five classes of statements (Daniel, Dibo-Cohen, Carité, Boyer, & Denis, 2007;Michon & Denis, 2001): Action prescription without referring to any landmark; action prescription referring to a landmark; reference to a landmark without referring to any associated action; descriptions of landmarks;…”
Section: Dependant Variablesmentioning
confidence: 99%
“…Their deficits include abnormal performance on delayed-response tasks (Park and Holzman, 1992; Goldman-Rakic, 1994; Glahn et al, 2003; Park et al, 2003; Saperstein et al, 2006; Genderson et al, 2007), figure search (Longevialle-Henin et al, 2005), mental rotation (de Vignemont et al, 2006; Halari et al, 2006), Gestalt perception (O'Donnell et al, 1996; Parnas et al, 2001; Cavezian et al, 2007; Kimhy et al, 2007), spatial span (Cannon et al, 2000; Perry et al, 2001; Manoach et al, 2005; Genderson et al, 2007; Thoma et al, 2007), 3-D real-world navigation Daniel et al (2007), and referencing (Landgraf et al, 2010a; Mazhari et al, 2010). According to a meta-analysis, there is an overall effect size of −1.00 regarding VS working memory deficits in chronic schizophrenia patients (Piskulic et al, 2007), and these deficits are independent of gender differences (Albus et al, 1997; Reichenberg et al, 2002; Voglmaier et al, 2005; Halari et al, 2006; Wolitzky et al, 2006).…”
Section: The Vision Perspective On Schizophreniamentioning
confidence: 99%
“…This, translates into a fragmented perception of the timing of events or, more specifically, a period of time divided into adjacent elements that is difficult to integrate into a unified experience that constrains (when did it occur?) as the main time interval in the conscious experience formation.The interior space was been described as a terrible emptiness that confirms it's collapsed aspect as mentioned above, thus ; reflecting a deformation and difficulty of the movement of thoughts due to the lack of the supreme coordinate "time" and because it is integrated in a spatio-temporal axis, Marie-Paule Daniel et al; affirm that « The reconstruction of the chronology of the landmarks is disrupted in schizophrenics, which confirms that the problem they are confronted with pertains to spatiotemporal coordination and affects the memory of the sequence in which landmarks have been encountered during the navigational episode.…”
Section: Back To the Physical Time: A Schizophrenic Patient Reveals His Tragedymentioning
confidence: 81%